Storage on Different Temperature and Testing for Effective to Germinate of the Rice Seed - KEODOUANGDY, manivanh; Phengkhamma, Tiengngeunh; Kittirath, Pisavanh; Keoyortou, Vilaysack; SengSouriya, Phoudthavong; Sakbouavong, Noumay (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study is about long storage of glutinous rice seed in order to process in drying, peal and starch, rice seed drying in the objectives was to study the appropriate temperature for storing rice grains and testing the germination efficiency of rice at different temperatures of 50℃, 55℃, 60℃, and 65℃, for periods of 6, 12, and 18 hours decreasing the moisture content which is cause of rice disease which is present in Dry-Oven rice seed by sunlight and use micro wave, it was paddy rice processing as 75% of standard moisture, therefore, it’s necessary to decrease moisture from rice seed, 12-14%. This Experiment was used micro wave in rice seed drying which is temperature of 50 , 55 , 60 , and 65 at the time period 6, 12 and 18 hours otherwise cam be divided in to two factors as Completely Randomized Design (CRD) which is 4 Treatments, Using Sirichai Analysis for least significant or not, then explain comparative statistic. From the Experiment can be seen that Drying-oven at temperature of 50 and 55 in 6 hours that is not significant, not suitable for Drying in order Decrease Moisture of rice seed at 60 and 65 between 12 and 18 hours are significant and suitable for glutinous rice Drying and Comparing at 50 , 55 , 60 , and 65 and It was Indicated that 12 and 18 hours can be decreased on the weigh of 12g and 14g which it means that 11 0,95 and 12 0,78 of the Moisture Standard of glutinous rice seed are 88% and 86% which is more Drying in 6 hours.